The assessment of the relation between the transverse abdominal muscle (TRA) and the occurrence of injuries and contusions at university students - Krystian Kałużny; Bartosz Kochański; Renata Szadkowska; Anna Kałużna; Michał Cichosz; Walery Zukow; Wojciech Hagner; Magdalena Hagner-Derengowska (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
PURPOSE: The aim of this study is the assessment of the relation between the transverse abdominal muscle (TRA) activity and the risk of occurrence of injuries and contusions as well as the number of injuries in a six-month observation. MATERIALS AND METHODS: The research was conducted in a group of 50 people, 29 men and 21 women. The assessment of the TRA activity was conducted with the use of Pressure Biofeedback Stabilizer (PBU) and the FMS test. The examined were divided into two groups. First comprises people with the proper transverse abdominal muscle activity, second consists of people with improper results. RESULTS: People with the proper transverse abdominal muscle activity gained higher average result (20,04 vs 18,11) and median value (20,00 vs 18,00) than people with the improper TRA activity according to the FMS test. The statistical analysis revealed that people with the improper TRA activity had statistically significant higher results in the FMS test than people with the improper TRA activity. The average number of injuries and contusions among people with the proper TRA activity equaled 0,70 (median 0,00), whereas, among people with the improper TRA activity equaled 1,92 (median 2,00). The statistical analysis revealed that people with the improper TRA activity had a statistically significant higher number of injuries and contusions during previous 6 months than people with the proper TRA activity. CONCLUSIONS: 1. The TRA activity has statistically significant effect on the risk of injuries and contusions occurrence, which according to the FMS test is higher among people with the improper TRA activity. 2. People with the improper TRA activity had remarkably higher number of injuries and contusions during previous 6 months than people with the proper TRA activity. 3. Statistically significant relation between the TRA activity and the number of injuries and contusions was demonstrated.